DESIGN AND FABRICATION OF CUTTING-EDGE PLASTIC BOTTLE CAP PRESS TOOLS FOR A GREENER FUTURE - Muhammad Aqdar Fitrah; Syaiful Syaiful; Hermin Hardyanti Utami (Acceleration: Multidisciplinary Research Journal, 2024)
Waste is the result of human activity which puts great pressure on the environment, especially when waste is not collected and ends up piling up in open places and water bodies. Waste management can generally be done by burning it, throwing it into ditches, landfilling it and most often throwing it into rivers. This design aims to deal with plastic waste by recycling it. The method used is a melting system using a microwave, while pressing uses a hydraulic jack. The use of this tool is to recycle the waste and process it into something that has use and sale value. The results of this bottle cap recycling tool convert plastic bottle cap waste into furniture material, in the form of coasters. The jack used in this tool has a capacity of 10 tons. In tests carried out on 125g bottle caps, they melted for 60 minutes at a temperature of 250°C.